Clinical characteristics of new psychoactive substances: A multicenter study. (January 2023) - Chen, Tse-Hao; Chen, Hsien-Yi; Lin, Chih-Chuan; Liu, Sung-Wei; Weng, Te- I.; Fang, Cheng-Chung; Yu, Jiun-Hao; Chen, Yen-Chia; Su, Yu-Jang
Abstract: Background: New psychoactive substances (NPS) are synthetic alternatives to illicit drug abuse that are not under international control but may pose a public health threat. Moreover, the symptoms and signs of NPS users may be quite variable. This study aimed to figure out the clinical characteristics of NPS users presented to the emergency department (ED). Methods: A total of 1385 cases were tested via urine toxicity screening from March 25, 2019, to January 28, 2020, in six medical centers, and ten hospitals, in Taiwan. A total of 123 non-NPS cases and 77 NPS-use cases were enrolled in this study. We compared the patient data–vital signs, presentation, co-morbidities, behaviors, symptoms, electrocardiograms, laboratory data, length of stays–and outcomes of NPS users and non-NPS drug users. Results: NPS users were 5.7 years younger than the non-NPS drug users (37 vs. 42.7 years, p = 0.022). Presently, NPS users had a 2.6-fold (27.2%) higher rate of suicide and a 2.9-fold (11.7%) greater possibility of violence than non-NPS drug users. Moreover, in NPS users, eye-opening was affected at a scale of 3.1 versus 3.4 (p = 0.048) in non-NPS drug users in the evaluation of consciousness and they experienced a 4.3-fold greater feeling of palpitation (p = 0.024) and had 8.1-fold higher chance of presenting facial flush (p = 0.032) than non-NPS drug users. Conclusion: NPS users are relatively younger, are more likely to experience facial flush and palpitation and engage in more self-harm, violence, and suicide than non-NPS drug users. Physicians need to pay attention to people who have altered, bizarre mental statuses with the clinical characteristics described above. Highlights: New psychoactive substance (NPS) users were 5.7 years younger than the non-NPS users. Although males still use more illicit drugs than females, the male: female ratio for NPS users (1.1) is lower than that of non-NPS users (3.2). NPS users are more likely to commit suicide (2.6-fold), cause self-harm (2.9-fold), and be prone to violence (2.9-fold) than non-NPS users. NPS users had 4.3-fold and 8.1-fold greater feeling of palpitations and facial flushes compared to non-NPS drug users.